2020
DOI: 10.1172/jci.insight.134852
|View full text |Cite
|
Sign up to set email alerts
|

A human amygdala site that inhibits respiration and elicits apnea in pediatric epilepsy

Abstract: BACKGROUND. Seizure-induced inhibition of respiration plays a critical role in sudden unexpected death in epilepsy (SUDEP). However, the mechanisms underlying seizure-induced central apnea in pediatric epilepsy are unknown. METHODS. We studied 8 pediatric patients with intractable epilepsy undergoing intracranial electroencephalography. We recorded respiration during seizures and during electrical stimulation mapping of 174 forebrain sites. A machine-learning algorithm was used to delineate brain regions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 68 publications
(84 reference statements)
9
75
0
Order By: Relevance
“…Studies indicate that ICA is a semiological phenomenon, hypothesized to arise from seizure activity in symptomatogenic brain regions, including mesial temporal structures (Lacuey et al, 2017;Vilella et al, 2019a). Recent investigations have shown that ictal activity that spreads to the amygdala elicits ICA (Nobis et al, 2020;Rhone et al, 2020). This finding supports previous observations that report that ICA preceded surface electroencephalographic onset of temporal lobe seizures, representing the first sign in 69% and occasionally the only clinical seizure manifestation (in 16% of the seizures) (Nadkarni et al, 2012;Lacuey et al, 2019a).…”
Section: Ica As a Semiological Phenomenonsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies indicate that ICA is a semiological phenomenon, hypothesized to arise from seizure activity in symptomatogenic brain regions, including mesial temporal structures (Lacuey et al, 2017;Vilella et al, 2019a). Recent investigations have shown that ictal activity that spreads to the amygdala elicits ICA (Nobis et al, 2020;Rhone et al, 2020). This finding supports previous observations that report that ICA preceded surface electroencephalographic onset of temporal lobe seizures, representing the first sign in 69% and occasionally the only clinical seizure manifestation (in 16% of the seizures) (Nadkarni et al, 2012;Lacuey et al, 2019a).…”
Section: Ica As a Semiological Phenomenonsupporting
confidence: 84%
“…However, we find recent evidence to suggest that with appropriate multimodal monitoring, these structures are highly symptomatogenic in both spontaneous seizures and ES, thus opening up a whole new aspect to epilepsy surgery assessments. From ES studies in animals and humans, we know that mesial temporal structures have a modulatory effect on breathing (Bailey and Sweet, 1940;Kaada et al, 1949;Kaada and Jasper, 1952;Dlouhy et al, 2015;Nobis et al, 2018;Lacuey et al, 2019b;Rhone et al, 2020). The mechanism underlying ICA is due to seizure discharge induced impairment of involuntary, suprapontine (amygdalohippocampal) breathing control through disruption of brainstem-driven inspiration (Lacuey et al, 2018c).…”
Section: Esis Signs and Symptoms: Central Apnea And The Symptomatogenic Zonementioning
confidence: 99%
“…Electrical stimulation of the human amygdala reliably produces apneas ( Dlouhy et al, 2015 ; Lacuey et al, 2019 ; Nobis et al, 2018 , 2019 ). This is likely related to the stimulation of structures of the extended amygdala rather than the lateral regions ( Nobis et al, 2018 ; Rhone et al, 2020 ). Similarly, seizure spread to these regions may be driving ictal apneas ( Dlouhy et al, 2015 ; Nobis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To localize the depth electrodes to the different subregions of the amygdala, we used the CIT168 atlas 77, 78 . Due to the bipolar reference scheme we utilized, we localized the resulting “virtual” electrodes using the averaged MNI coordinates of the two referenced electrodes.…”
Section: Methodsmentioning
confidence: 99%